Association between endometriosis and working life among Danish women - Røssell, Eeva-Liisa; Plana-Ripoll, Oleguer; Josiasen, Marie; Hansen, Karina Ejgaard; Bech, Bodil Hammer; Rytter, Dorte (Human reproduction (Oxford), 2025)
What is the association between endometriosis and working life (lost), workforce participation, and productivity? Women with endometriosis experienced more working years lost due to disability pension and to a smaller degree sick leave, they were less frequently working or enrolled in education, had more sick days, were less productive, and had lower work ability. Endometriosis is associated with negative consequences on working life; however, previous studies are based on self-reported data or smaller samples of women. To the best of our knowledge, no previous studies have quantified the average reduction in working hours during the entire span of working life using population-based registers. This study included two Danish data sources. In the register-based cohort study (main analysis), a total of 2 650 554 women aged 18-65 years were followed for a total of 42.8 million person-years from 1992 to 2021. In the questionnaire-based cross-sectional study (Supplementary Analysis), 35 490 women aged 26-51 years were invited to participate and 7298 women completed the questionnaire. For the main analysis, 42 741 (1.6%) were diagnosed with endometriosis. We estimated working years lost decomposed into disability pension, voluntary early retirement, or death for women with endometriosis and the general female population. For the supplementary analysis, 270 (4.0%) reported to have endometriosis. We analysed these recent questionnaire data on women's health to further investigate working life and productivity among women with and without endometriosis. Based on the main analysis, women with endometriosis lost on average an additional 0.26 years (95% CI: 0.17-0.37) of working life compared to the general female population. This was due to sick leave and especially disability pension. For the supplementary analysis, the participation rate was 20.6%. Women with endometriosis reported to be less frequently working or enrolled in education (74.1% (95% CI 68.4%-79.2%) with endometriosis, 82.7% (95% CI 81.8%-83.7%) without) and had more sick days (4-28 sick days last 4 weeks: 16.2% (95% CI 11.6%-21.8%) with endometriosis, 7.9% (95% CI 7.2%-8.7%) without). In addition, they reported lower productivity and work ability. Endometriosis is underdiagnosed in the register data as only hospital diagnoses are registered and diagnoses from private practicing gynaecologists and general practitioners are missing. In addition, sick leave might be underestimated as shorter periods of sick leave are not included in the registers. Questionnaire data were self-reported including endometriosis and participants might be a selected group of women. This study is in line with previous studies on endometriosis and its impact on working life. In addition, to the best of our knowledge, no previous study has quantified the average reduction in working years over the entire working life. However, the findings might only be generalizable to a Danish or Nordic context as these countries have welfare systems with economic security during unemployment, periods with illness, or reduced ability to work. This study is supported by a grant from the project 'Finding Endometriosis using Machine Learning' (FEMaLe/101017562), which has received funding from The European Union's Horizon 2020 research and innovation programme. The authors have no conflicts of interest. N/A.